Business methodology to integrate social networking into ecommerce alternatives: Olive Tree Foods Ltd. - Hossain, Nafisa Tasnuva (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.